Seeking the Roots of Terrorism: An Islamic Traditional Perspective - Yo, Mbaye (Journal of religion and popular culture, 2005)
This article analyzes the associational relationship between Islam and terrorism as embedded in the current popular culture. Two questions are examined: (a) whether from a historical and political perspective current organizations that are terror threats and Bin Laden are natural outgrowths of the Islamic tradition; (b) whether the Muslim popular tradition has historically interpreted some Qur'anic terms such as Jihad and Kuffar "allegedly infidels" to promote hate and violence against non-Muslims. In view of this discussion, the article suggests that the current terror treats is due to the politicization of the Muslim faith, rather than rooted in Islamic teachings.